2021
DOI: 10.1186/s12912-021-00563-w
|View full text |Cite
|
Sign up to set email alerts
|

How does the self-reported health of undergraduate nursing students change during their degree programme? Survey results from a Scottish University

Abstract: Background The lifestyle behaviours, and the physical and mental health of nurses, are poorer than those of other allied health professionals, and of the general population. However, these were no less favourable among first year undergraduate nursing students at a Scottish Higher Education Institution (HEI) than among similar people of the same age. We compared health and health behaviours among the same cohort of undergraduate nursing students over the course of their degree. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
2
2
1
Order By: Relevance
“…Nevertheless, 4 out of 10 students reported sleep problems. This is in contrast to previous research among nursing students, where only 1 in 10 students reported sleep problems during the first year of higher education [ 39 ] although sleep problems did increase during the third year [ 40 ]. Sleep could have an impact on anxiety and depression [ 13 ], and is essential to serve several important physical functions, such as recuperation from infectious diseases and consolidation of memories [ 48 ].…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…Nevertheless, 4 out of 10 students reported sleep problems. This is in contrast to previous research among nursing students, where only 1 in 10 students reported sleep problems during the first year of higher education [ 39 ] although sleep problems did increase during the third year [ 40 ]. Sleep could have an impact on anxiety and depression [ 13 ], and is essential to serve several important physical functions, such as recuperation from infectious diseases and consolidation of memories [ 48 ].…”
Section: Discussioncontrasting
confidence: 98%
“…In the results, most students reported good general health and good general well-being. This is consistent with previous research among nursing students [ 39 ]; however, previous studies have also found that general health and well-being decline during the 3-year bachelor programme [ 40 ]. Examples of health-promoting strategies that higher education can implement to maintain good general health and general well-being and create more incentives for a health-promoting perspective include integrating knowledge of sustainable working life into the programme through the courses’ content and pedagogical structure.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Extant research highlights how financial stressors are a predictor of both physical and mental health problems (Cutherbertson et al, 2004) and difficulties with disclosure and the stigma of mental health help-seeking (Quinn et al, 2009). Further work has emphasised the importance of close relationships in moderating the effect of depressive symptoms on declining mental health, reduced physical activity and suicidal ideation over the course of a degree course (Evans et al, 2021;Murray et al, 2016). Such research has, however, tended to be specific to one HEI and/or student population and thus further, targeted work is needed to understand the broader mental health issues and research priorities facing diverse student populations throughout Scotland .…”
Section: Why Focus On the Scottish Context?mentioning
confidence: 99%